2021
DOI: 10.3390/curroncol28020136
|View full text |Cite
|
Sign up to set email alerts
|

On the Prognosis of Multifocal Glioblastoma: An Evaluation Incorporating Volumetric MRI

Abstract: Primary glioblastoma (GBM), IDH-wildtype, especially with multifocal appearance/growth (mGBM), is associated with very poor prognosis. Several clinical parameters have been identified to provide prognostic value in both unifocal GBM (uGBM) and mGBM, but information about the influence of radiological parameters on survival for mGBM cohorts is scarce. This study evaluated the prognostic value of several volumetric parameters derived from magnetic resonance imaging (MRI). Data from the Department of Neurosurgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In multivariate Cox regression, however, only resection and adjuvant therapy retained statistical significance. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In multivariate Cox regression, however, only resection and adjuvant therapy retained statistical significance. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…In multivariate Cox regression, however, only resection and adjuvant therapy retained statistical significance. [15] In a study by Kong et al, total 20 out of 51 treatment naïve GBM patients had mGBM. Kaplan-Meier survival analysis suggested that multicentric mGBM patients had worse title, year of study, authors name, year, country of origin, total number of patients, total number of patients with mGBM, mean age, gender, KPS/performance status (in any other reported scale), treatment details (extent of surgery/ radiotherapy/chemotherapy), and information on survival outcome were collected [Table 2].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this day MRI remains the most used imaging modality for glioblastoma diagnosis and evaluation of treatment response and prognosis [ 1 , 4 , 10 ]. A number of advanced MRI techniques such as functional MRI (fMRI), diffusion tensor imaging (DTI), and MRS have been adopted for tumor treatment including preoperative surgical planning or as an instrument to distinguish post-operative vascular damage from residual enhancing tumor[ 9 , 12 , 13 , 39 ]. However, it is highly challenging to assess sub-regions of tumors in MRI scans visually because of their anatomic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Only some 6.8% of glioblastoma patients survive beyond five years [ 2 ]. As the most common non-invasive imaging technique to assess glioblastoma [ 3 , 4 ], magnetic resonance imaging (MRI) has been employed as a diagnostic instrument for glioblastoma diagnosis, prognostication, and monitoring of therapy response [ 5 – 9 ]. Other methods, such as diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC), perfusion-weighted imaging (FWI), and magnetic resonance spectrum imaging (MRS) are also widely used in addition to conventional sequences [ 4 , 6 , 7 , 10 13 ].…”
Section: Introductionmentioning
confidence: 99%